Improper cause-of-death statements by specialty of certifying physician: a cross-sectional study in two medical centres in Taiwan. Issue 4 (31st July 2012) - Cheng, Tain-Junn; Lee, Fang-Chuan; Lin, Shio-Jean; Lu, Tsung-Hsueh
Abstract : Objective: To determine the frequency of various types of improper cause-of-death (COD) statements reported on death certificates and whether the frequency differed by specialty of the certifying physician. Design: Cross-sectional descriptive study. Setting: 2 medical centres in Tainan, Taiwan. Participants: A total of 2520 death certificates issued by 230 physicians. Main outcome measures: 4 types of improper COD statements based on the criteria of correctness of the COD causal sequence and the level of specificity of underlying COD selected. Results: Of 2520 death certificates analysed, 502 (19.9%) had at least one type of improper COD statement. However, only 235 (9.3%) sustained major errors, that is, 91 (3.6%) reported incorrect causal sequence and 144 (5.7%) reported only mechanism(s) of death (such as respiratory failure, heart failure, sepsis and acidosis). The improper reporting rate was highest among nephrologists (53%, 24/45), followed by infectious diseases physicians (45%, 29/65) and was lowest among oncologists (6%, 57/995). Conclusions: About one-fifth issued death certificates sustained improper COD statements and only one-tenth had noteworthy errors that would threaten the quality of COD statistics. The frequency varied by specialty of the certifying physician because physicians in different specialties manage different types of diseases and conditions with contrasting complexities in terms of determining the causal sequence and specificity of COD statements.